In the shadow of the ‘government of the left’: the 2019 legislative elections in Portugal - Jalali, Carlos (2020)
This article examines the Portuguese 2019 legislative election, which took place after a period of unprecedented and unexpected cooperation of the pro-European centre left and eurosceptic radical left. Initially dismissed as a ‘contraption’, this alliance belied the initial expectations and increasingly became a reference for South European social democratic parties. Yet, despite a seemingly reinforced popular mandate, it was not maintained after the 2019 election. We identify three factors for this. First, we suggest that the 2015–19 ‘contraption’ was a case of weak contract parliamentarism, making it easier not to renew. Second, the electoral victory of the Socialist Party made deals between the left-wing parties less necessary. Third, enduring programmatic differences between those parties hindered cooperation. Finally, it should be noted that the ‘contraption’ impacted interparty relations on the left and the expansion in the number of parliamentary parties in 2019, notably on the right.